Targeting USP1 Potentiates Radiation‐Induced Type I IFN‐Dependent Antitumor Immunity by Enhancing Oligo‐Ubiquitinated SAR1A‐Mediated STING Trafficking and Activation - Weilin Zhou; Yuxuan Zhao; Wenjing Qin; Weijian Wu; Chenyang Liao; Yiqiu Zhang; Xingli Yang; Xue Chen; Youqiao Wang; Yushan Kang; Jiaxin Wu; Jiaojiao Zhao; et al. (Advanced Science)
Abstract The magnitude of Type I interferon (IFN) mediated innate immune response within the tumor microenvironment (TME) critically influences the effectiveness of radiotherapy. Unfortunately, due to a myriad of resistance mechanisms, the double‐stranded DNA (dsDNA) signals produced by tumor cells postradiotherapy often induce a diminished response from immune cells. Through chemical screening targeting deubiquitinating enzymes, we identified USP1 (Ubiquitin Specific Peptidase 1) inhibitor as an enhancer of post‐radiotherapy dsDNA responses. Mechanistically, within the context of immune‐stimulatory cells in TME, USP1 serves as a suppressor in the stress‐mediated stages of the cGAS (Cyclic GMP‐AMP synthase) ‐STING (Stimulator of interferon genes protein) signaling pathway, specifically affecting the trafficking of STING from endoplasmic reticulum to Golgi apparatus. It is elucidated that SAR1A (Secretion associated Ras related GTPase 1A) requires K27‐linked oligo‐ubiquitination to assemble the STING‐COP‐II (Coat protein II) transport complex for STING trafficking. USP1 counteracts this activation by removing SAR1A ubiquitination, thereby blocking STING trafficking and activation. Consequently, pharmacological USP1 inhibition using ML323 sustains SAR1A ubiquitination and COP‐II complex formation, significantly enhancing STING trafficking and subsequent Type I IFN production. This intervention substantially amplifies radiotherapy‐induced immune activation in the TME, providing a strategic approach to overcome therapeutic resistance and synergize radiotherapy with immunotherapies.